2011
DOI: 10.1038/onc.2011.39
|View full text |Cite
|
Sign up to set email alerts
|

KiSS1 mediates platinum sensitivity and metastasis suppression in head and neck squamous cell carcinoma

Abstract: Although surgery and radiotherapy have been the standard treatment modalities for head and neck squamous cell carcinoma (HNSCC), the integration of cisplatin (CDDP)-based therapy has led to improvements in local and regional control of disease for patients. However, many trials show that only 10–20% of patients benefit from this treatment intensification, which can result in profound treatment-associated morbidity and mortality. Moreover, the marginal survival improvement suggests that CDDP resistance is an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 42 publications
(42 reference statements)
7
38
0
Order By: Relevance
“…It has been shown in a variety of cell types that the cytotoxic effect of cisplatin is due to activation of p53 and induction of apoptosis (15, 21-23). Previous studies with HNSCC cells have also reported a similar finding (2, 4, 24-26). However, the cisplatin doses used in all of these studies were 10-50 folds higher than the clinically achievable dose of cisplatin.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…It has been shown in a variety of cell types that the cytotoxic effect of cisplatin is due to activation of p53 and induction of apoptosis (15, 21-23). Previous studies with HNSCC cells have also reported a similar finding (2, 4, 24-26). However, the cisplatin doses used in all of these studies were 10-50 folds higher than the clinically achievable dose of cisplatin.…”
Section: Introductionsupporting
confidence: 81%
“…Cisplatin, which forms the basis of chemotherapy regimens used for HNSCC treatment, is not effective as a single agent in many patients. Multiple studies have attributed resistance of tumors to cisplatin to reduced drug uptake, increased drug detoxification process, enhanced DNA repair, and suppressed apoptotic response of resistant cells; while others have sought to link the cisplatin responses in HNSCC to the expression levels of certain biomolecules (4, 19, 21, 22, 41). TP53, the tumor suppressor gene, is one such biomolecule found to be mutated in about 60-80% of HPV negative HNSCC specimens (6, 42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein extraction and western blotting Assays were performed as described previously by Jiffar et al 39 The antibodies are listed in Supplementary Table 7.…”
Section: Lentivirus Production and Transductionmentioning
confidence: 99%
“…In addition, the identification of potential molecular biomarkers of HNSCC could be clinically useful for predicting prognosis and therapeutic efficacy, and also in the development of targeted therapies. To better understand tumor metabolism of HNSCC, most studies have been carried out on HNSCC cells that have been cultured in vitro (Schmitz and Machiels, 2010, Sandulache et al, 2011, Jiffar et al, 2011), and tumor tissues obtained from in vivo conditions (Karahatay et al, 2007, Ziebart et al, 2011). Biomarkers associated with HNSCC that have been identified from tissues or serum/plasma, revealed considerable alterations in protein expression.…”
Section: Introductionmentioning
confidence: 99%